2020
DOI: 10.1002/hbe2.219
|View full text |Cite
|
Sign up to set email alerts
|

Theorizing technology and behavior: Introduction to special issue

Abstract: What is "behavior"? What is "technology"? What is the relation between behavior and technology? In an effort to address these fundamental questions and provide the field with a more solid and coherent theoretical foundation, we assembled a special issue wherein scholars from various academic fields (psychology, economy, communication, science education, learning sciences, and anthropology) theorize what it means to "behave with a technology." We begin by presenting the literature that sparked these questions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…MOOCs and the Task-Technology Fit. Technology is an important driving force behind individual behavior depending on the situation [47]. Considering the characteristics of the MOOC environment, the relationship between technology use and the subsequent progress of the user needs to be structurally examined; the task-technology fit is useful for this purpose.…”
Section: Continuance Intention To Use and Basic Psychologicalmentioning
confidence: 99%
“…MOOCs and the Task-Technology Fit. Technology is an important driving force behind individual behavior depending on the situation [47]. Considering the characteristics of the MOOC environment, the relationship between technology use and the subsequent progress of the user needs to be structurally examined; the task-technology fit is useful for this purpose.…”
Section: Continuance Intention To Use and Basic Psychologicalmentioning
confidence: 99%
“…Johnson [ 32 ] said that workplace bullying is not created due to a state of isolation; rather, it is preceded by each of these layers, and identifying effective responses to and informing all about these interconnected opportunities are essential. Similarly, Oliveira [ 33 ] indicated that contemporary organisations’ technology is a driving force that shapes individual behaviour. Therefore, technology has a direct influence on reshaping human and individual behaviour.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nowadays, overcoming the physical constraint typical of face-to-face communications allows people to have a revolutionary way to process information, working together and optimizing time and space in order to interact economically with multiple groups [47,48]. In fact, the possibility to "incarnate" and experience multiple social identities and to belong to a higher number of groups was enormously amplified thanks to the expansion of communication possibilities introduced by ICTs as personal computers, televisions, email systems, smart devices, and internet-enabled systems [49] that people promptly learned and become proficient in using for their purposes [50,51]. In particular, one of these emerging technologies as social networks made the maintenance and the transmission of social evaluations much easier through some technical features such as the manifest approval of user's contents.…”
Section: Introductionmentioning
confidence: 99%